2001
DOI: 10.1163/156856801741332
|View full text |Cite
|
Sign up to set email alerts
|

Detecting binocular 3D motion in static 3D noise: no effect of viewing distance

Abstract: Abstract.Relative binocular disparity cannot tell us the absolute 3-D shape of an object, nor its 3-D trajectory if it is moving, unless the visual system has independent access to how far away the object is at any moment. Indeed, as the viewing distance is changed, the same disparate retinal motions will correspond to very different real 3-D trajectories. In this paper we were interested in whether binocular 3-D motion detection is affected by viewing distance. We used a visual search task in which the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For example, oscillatory motion thresholds are lower when the half-images oscillate in-phase (translation) compared to when they are in anti-phase (i.e., motion in depth) (Sumnall & Harris, 2002;Tyler, 1971;Tyler & Cavanagh, 1991;Westheimer, 1990). Similarly, the half-images of a motion-in-depth stimulus (equal and opposite lateral motions) are much more easily detected amidst noise than their fused combination (Harris, McKee, & Watamaniuk, 1998;Harris & Sumnall, 2000). McKee and Harrad (1993) found that monocular vernier acuity was much higher than when the same vernier target was interocularly paired with an offset vernier target that produced a standing disparity of 4 arcmin between the upper and lower lines of the target.…”
Section: Introductionmentioning
confidence: 99%
“…For example, oscillatory motion thresholds are lower when the half-images oscillate in-phase (translation) compared to when they are in anti-phase (i.e., motion in depth) (Sumnall & Harris, 2002;Tyler, 1971;Tyler & Cavanagh, 1991;Westheimer, 1990). Similarly, the half-images of a motion-in-depth stimulus (equal and opposite lateral motions) are much more easily detected amidst noise than their fused combination (Harris, McKee, & Watamaniuk, 1998;Harris & Sumnall, 2000). McKee and Harrad (1993) found that monocular vernier acuity was much higher than when the same vernier target was interocularly paired with an offset vernier target that produced a standing disparity of 4 arcmin between the upper and lower lines of the target.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the human visual is sensitive to the retinal binocular disparity, and its change when objects move, which we express in angular units, rather than being specifically sensitive to the depths between points or objects in the world [4][5][6] . In human vision, we therefore define binocular disparity in terms of angles subtended at the eye, rather than in display-screen units, such as pixels.…”
Section: Background: Binocular Disparity As Defined In Human Vision Smentioning
confidence: 99%
“…Harris, McKee, and Watamaniuk (1998) showed that the detection of motion-in-depth was more affected by disparity noise than was the detection of lateral motion, and they suggested that the detection of 3D motion was carried out by static disparity mechanisms rather than specific mechanisms sensitive to the change of disparity over time. Using the same paradigm, Harris and Sumnall (2000) showed that there was no effect of the viewing distance on the detection of 3D and 2D motion, suggesting that motion-in-depth detection is based on relative and not absolute signals.…”
Section: Introductionmentioning
confidence: 96%